Searching for targets within the spatial layout of visual short-term memory. - Kuo, B; Rao, A; Lepsien, J; Nobre, A (2009)
Recent studies have revealed that the internal representations that we construct from the environment and maintain in visual short-term memory (VSTM) to guide behavior are highly flexible and can be selectively modulated according to our task goals and expectations. In the current study, we conducted two experiments to compare and contrast neural mechanisms of selective attention related to searching for target items within perceptual versus VSTM representations. We used event-related potentials to investigate whether searching for relevant target items from within VSTM representations involves spatially specific biasing of neural activity in a manner analogous to that which occurs during visual search for target items in perceptual arrays. The results, replicated across the two experiments, revealed that selection of a target object within a search array maintained in VSTM proceeds through a similar mechanism as that in the perceptual domain. In line with previous results, N2pc potentials were obtained when targets were identified within a perceptual visual-search array. Interestingly, equivalent N2pcs, with similar time courses and scalp distributions, were also elicited when target items were identified within a VSTM representation. The findings reinforce the notion of highly flexible VSTM representations that can be modulated according to task goals and suggest a large degree of overlap in the spatially specific neural mechanisms of target selection across the perceptual and VSTM domains.